Calcite Removal From Carbonated Water - Uranium In Situ Leaching System (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1985)
A method has been developed to remove calcite from the leaching circuit in the uranium in situ leaching system. The process involves injecting the leachate and a pH control agent tangentially into an inverted cone reactor containing calcite seed catalyst. The leachate can be treated at high throughput to obtain clear effluent containing 5 ppm or lower Ca. Both lime and ammonia are effective pH control agents and consumed according to stoichiometry.